1999
DOI: 10.1200/jco.1999.17.2.697
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Liposomal Vincristine

Abstract: The ability to administer elevated doses of vincristine, as well as indications of efficacy, suggests that ONCO-TCS warrants further clinical investigation in a phase II setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 15 publications
0
41
1
Order By: Relevance
“…29 ± 31 These findings were subsequently extended and confirmed in Phase I/II clinical trials, which have demonstrated the beneficial effects of liposome encapsulation in regard to improved pharmacokinetics and antitumor activity of liposomal vincristine in humans. 32,33 The improved antitumor efficacy of SALP over free [ S] ODNs is consistent with the increased tumor accumulation and homogeneous distribution of [ S] ODNs within the NG tumors. The broad distribution of SALP/ FITC ± [ S] ODNs within the NG tumor mass was confirmed using LSCM analysis.…”
Section: Discussionmentioning
confidence: 55%
“…29 ± 31 These findings were subsequently extended and confirmed in Phase I/II clinical trials, which have demonstrated the beneficial effects of liposome encapsulation in regard to improved pharmacokinetics and antitumor activity of liposomal vincristine in humans. 32,33 The improved antitumor efficacy of SALP over free [ S] ODNs is consistent with the increased tumor accumulation and homogeneous distribution of [ S] ODNs within the NG tumors. The broad distribution of SALP/ FITC ± [ S] ODNs within the NG tumor mass was confirmed using LSCM analysis.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, total plasma VCR exposure following the administration of VSLI appears to be greater than that of conventional VCR because of the difference in elimination. The liposomal encapsulation of VCR protects the drug from the early phase of rapid elimination that is observed with nonliposomal VCR [15] . Previous studies have demonstrated that increasing VCR retention in liposomal systems improves the therapeutic index by increasing the duration of drug exposure to the tumor tissue [8,10,[16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that compounds that regulate the polymerization states of microtubules may be used to enhance transfection efficiency by preventing liposome-DNA complexes from degrading in lysosomes. In addition, microtubule inhibitors such as vincristine, 15,16 and microtubule stabilizers such as taxol, 17 are often used in the treatment of cancer, although the effective concentration of these substances often overlaps their toxic dose range. Since it has been reported that encapsulation of these drugs in liposomes is an effective way to reduce their toxicity, [15][16][17][18] gene delivery using liposomes in the presence of such drugs to treat cancer might be a powerful technique due to the dual effects of gene therapy and chemotherapy.…”
Section: Figure 4 Effects Of Nocodazole and Taxol On The Distributionmentioning
confidence: 99%